African Biodiversity & Conservation: an open access, free to publish journal for research on African biodiversity and conservation - Magee, Anthony R.; Wilson, John R. (African Biodiversity & Conservation, 2026)
In this editorial we provide an overview of the journal African Biodiversity & Conservation (ABC, www.abcjournal.org/): ‘A journal that publishes scientifically robust peer-reviewed studies on African biodiversity and conservation in a manner that is free, accessible, and ethical and that maintains high quality standards throughout’. We see the scope of the journal as self-explanatory–A. the research must be directly on African issues; B. it must be focussed on biodiversity; C. there should be a link through to conservation management and policy in a broad sense; and finally the research must be well conducted and noteworthy. The aim is to be inclusive, ABC will not chase impact factors. We provide various examples of what ABC regards as noteworthy and what sorts of submissions are not considered, noting that parochial articles will be considered if they link to broader lessons or a broader audience, otherwise a local or more discipline-specific journal would be more suited. We also evaluate how ABC currently addresses the various developing international standards in biodiversity data management and publishing ethics. The journal is indexed in the Directory of Open Access Journals (DOAJ), is listed on the ISI Web of Science, and aims to support FAIR data standards, and meet the principles of Plan S. ABC follows a largely traditional model with a growing board of associate editors relying on reviewers from Africa and elsewhere to ensure a robust and scientifically rigorous peer-review process. Unlike many other journals, the production team of ABC is in-house, allowing us to ensure that production standards are high. Finally, we briefly review related journals and note that ABC is one of only four ISI-listed platinum open access journals focussing on African biodiversity. The journal is financially supported by, but editorially independent from, the South African National Biodiversity Institute (SANBI). There is no requirement on readers or authors to pay for access, although if a research grant provides funds for paying author page charges, we are keen to establish the principle that SANBI should not subsidise such publications. Please get in touch if you are keen to be involved in the journal in whatever capacity. We welcome input, advice, criticism, but most of all noteworthy submissions on African biodiversity and conservation.